Bringing Farmers Back into Breeding: Experiences with Participatory Plant Breeding and Challenges for Institutionalisation - Almekinders, Conny J.M.; Hardon, Jaap (Agromisa, 2006)
The purpose of this report is to provide an overview of Participatory Plant Breeding (PPB). It reviews the approach from both a technical and a social perspective and identifies the challenges for incorporating PPB in national plant breeding regimes...